Avaliação in vitro da atividade antifúngica do óleo de coco ozonizado contra Candida spp - Mendes, Mário Luís Tavares (2017)
Denture Stomatitis (DS) is a pathology characterized by the erythematous, diffuse or dotted aspect of the palatal mucosa under the prosthesis. DS has a multifactorial etiology, however Candida infection is a more common cause. This oral lesion presents different degrees of severity ranging from petechiae to a generalized inflammation with papillary hyperplasia. The conventional treatment for DS consists of the combination of antifungal, oral hygiene and prosthesis. However, an increase in yeast resistance to existing conventional treatments is observed. Therefore, is important to develop new treatments. For this purpose, the study carried out an in vitro evaluation of the antifungal activity of ozonized coconut oil (OCO) against Candida spp isolates collected from patients diagnosed with DS. Were collected samples of biological material of the mucosa and prosthesis of patients with diagnosis of DS. We identified the species of the samples with chromagar medium. The evaluation of the antifungal activity was performed by microdilution assays using the CLSI-M27-A3 protocol. The tested substance was OCO and the positive control of the assays was nystatin. The observation of cell viability was performed with trypan blue and counting in the Neubauer chamber in optical microscope. The following tests used in the statistical analysis was the kolmogorov-Sminorv, Anova one-way with post hoc test Dunnett’s, Linear Trend. The p <0.05 value was considered significant. 50% of the patients with DS were female. The mean age and standard deviation was 47.5±4.5 years and the average length of use the prosthesis and standard deviation was 19 ±9 years. In total, 15 isolates of candida were obtained, the species C. albicans the most prevalent with 44%, followed by C. glabrata (25%), C. tropicalis (19%), C. krusei and other species with 6% each. C. albicans colonized more the palatal mucosa and C. glabrata more the prosthesis. The OCO at concentrations of 5.0% (p <0.001) and 7, 5% (p <0.0001) showed fungicidal activity against the candida isolate and the four species obtained from the patient with DS and this activity was dose dependent (p< 0.0001). The significant antifungal activity of OCO suggests that they could serve as a source of compounds with therapeutic potential in the treatment of Denture Stomatitis. However, pharmacokinetic studies are necessary to understand its mechanisms of action, toxicity, drug interactions, and proper dosing in order to proceed to in vivo clinical studies.